Ethics across the curriculum: Detecting and describing emergent trends in ethics education. (December 2020) - Kidd, David; Miner, Jess; Schein, Maggie; Blauw, Michael; Allen, Danielle
Highlights: Automated analysis of course catalogs reveals opportunities for ethics education across the curriculum. Instructors report a wide range of pedagogical methods and goals related to ethics education. Instructors' methods and goals can be understood in terms of existential, civic, and vocational development. Abstract: This paper presents an inclusive and emergent approach to identifying ethics courses and revealing their pedagogical methods and goals. It outlines a two-year study of undergraduate and professional courses at a private university addressing ethical themes. The study began with three assumptions: 1) ethics education occurs across the curriculum; 2) instructors are master practitioners with learning theories and goals that are often implicit; and 3) education contributes to three domains of human development: existential, civic, and vocational. These principles informed the development of a method for describing ethics education based on instructor reports of what and how they teach. Results of an application of this method are presented, and implications for ethics teaching and assessment in higher education are discussed.